À la lettre (près) : autoportraits de Ralph Eugene Meatyard - Jean-Marc VICTOR (E-REA)
This paper proposes to question American photographer Ralph Eugene Meatyard’s tendency to integrate various manifestations of the written sign into a number of his self-portraits. To what extent does the mediation of scriptural forms (if indeed “mediation” is the appropriate term) influence the modes of photographic self-representation as the relation between what can be seen and what can be read in these self-portraits seems to oscillate between equivalence, substitution, complementarity and interference? After a short reminder of the theoretical and historical links between photographic self-portraits and writing, five of such self-portraits by Meatyard are analyzed in order to shed light on this issue.